2006
DOI: 10.1007/s00330-006-0379-y
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings predicting the outcome of cervical facet joint blocks

Abstract: To determine which crosssectional imaging findings predict the short-term outcome of cervical facet joint blocks (FJB) and to evaluate the effect of combined intra-/periarticular versus periarticular injection on pain. Fifty facet joints in 37 patients were included in the study. Single, unilateral FJBs in 24 patients, and bilateral single level FJBs in 13 patients were performed, respectively. In all patients, pain relief was assessed using a visual analogue scale. All computed tomography (CT) examinations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 16 publications
0
10
0
1
Order By: Relevance
“…The indirect cervical nerve root injection is similar to the technique used for CT-guided cervical facet joint infiltration [25], except that there is no attempt to place the needle into the joint itself and the non-particulate corticosteroid preparation dexamethasone is used instead of a crystalloid corticosteroid. Serious adverse effects in image-guided cervical facet joint infiltration are rare [26].…”
Section: Discussionmentioning
confidence: 99%
“…The indirect cervical nerve root injection is similar to the technique used for CT-guided cervical facet joint infiltration [25], except that there is no attempt to place the needle into the joint itself and the non-particulate corticosteroid preparation dexamethasone is used instead of a crystalloid corticosteroid. Serious adverse effects in image-guided cervical facet joint infiltration are rare [26].…”
Section: Discussionmentioning
confidence: 99%
“…8183 Unfortunately, most imaging studies to date have not used reliable and well-developed scales for assessment of FJ OA. Owing to the lack of specificity of FJ OA on imaging, anaesthetic blockade using fluoroscopically guided injections has become standard practice for diagnosing whether a particular joint is producing pain.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“… 5 Furthermore, many studies have also reported that the severity of spinal stenosis or facet arthropathy were not related to ESI or FJI effect. 21 , 22 As such further studies for why these treatments are more effective in non-operated patients should be conducted. Neurogenic claudication, a characteristic symptom of spinal stenosis, limits daily lives of patients or their motions and has a great effect on their quality of life.…”
Section: Discussionmentioning
confidence: 99%